Inclusion (Boston, Massachusetts : Harvard Business Review Press, 2023)
"We all want our colleagues to feel safe, heard, and free to be their authentic selves at work. But being an inclusive colleague doesn't happen overnight-it's an evolving process that involves growing, learning, and intentional effort. This book will teach you how to address and understand your biases, how to get better at noticing and responding to microaggressions, and why being an inclusive colleague will spark more-productive and -rewarding relationships with your coworkers and boss. With the latest psychological research and practical advice from leading experts, you'll learn how to make your workplace more inclusive and culturally competent-starting with yourself"--
Why Inclusive Leaders Are Good for Organizations : Six behaviors to model when practicing inclusive leadership / by Juliet Bourke and Andrea Titus -- The Value of Belonging at Work : It's beneficial for people -- and for the bottom line / by Evan W. Carr, Andrew Reece, Gabriella Rosen Kellerman, and Alexi Robichaux -- Make Psychological Safety a Strategic Priority : How leaders can enhance integrity, innovation, and inclusion / by Maren Gube and Debra Sabatini Hennelly -- The Importance of Being an Inclusive Colleague : Three ways to make a meaningful difference to you-and your peers-performance / by Juliet Bourke -- Recognizing and Responding to Microaggressions : What to do if you witness a microaggression or commit one / by Ella F. Washington -- Tap Into Empathy : Treat others how they want to be treated / by Irina Cozma -- Inclusion Starts with Belonging : It's time to unlearn our own biases, especially the ones we have against ourselves / by DDS Dobson-Smith -- Stop Using These Words and Phrases : The language we use can cause others to feel hurt, disrespect, and isolation / by Rakshitha Arni Ravishankar -- The Power of Sharing Our Stories : Storytelling gives us a rare chance to take on a new perspective / by Selena Rezvani and Stacey A. Gordon.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 20, 2023).
WorldCat record variable field(s) change: 050
Keywords: Work environment -- Psychological aspects; Belonging (Social psychology); Diversity in the workplace; Leadership; Belonging (Social psychology); Diversity in the workplace; Leadership; Work environment -- Psychological aspects